The Role of Information Technologies in the Formation of the Spiritual World View of Youth - Abdulhakimova Fatima Turdiqul qizi (Research Parks Publishing LLC, 2022)
This article discusses the role of information technology in the formation of the worldview of young people and its growing importance in today's era of technical and technological development. In addition, the extent to which information and information technologies affect the morale of young people and whether it occurs on a positive or negative basis. Our article on these effects is based on examples.